In silico evidence implicating novel mechanisms of Prunella vulgaris L. as a potential botanical drug against COVID-19-associated acute kidney injury - Yang, Xue-Ling; Wang, Chun-Xuan; Wang, Jia-Xing; Wu, Shi-Min; Yong, Qing; Li, Ke; Yang, Ju-Rong (Frontiers in Pharmacology, 2023)
COVID-19-associated acute kidney injury (COVID-19 AKI) is an independent risk factor for in-hospital mortality and has the potential to progress to chronic kidney disease. Prunella vulgaris L., a traditional Chinese herb that has been used for the treatment of a variety of kidney diseases for centuries, could have the potential to treat this complication. In this study, we studied the potential protective role of Prunella vulgaris in COVID-19 AKI and explored its specific mechanisms applied by network pharmacology and bioinformatics methods. The combination of the protein-protein interaction network and Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment -target gene network revealed eight key target genes (VEGFA, ICAM1, IL6, CXCL8, IL1B, CCL2, IL10 and RELA). Molecular docking showed that all these eight gene-encoded proteins could be effectively bound to three major active compounds (quercetin, luteolin and kaempferol), thus becoming potential therapeutic targets. Molecular dynamics simulation also supports the binding stability of RELA-encoded protein with quercetin and luteolin. Together, our data suggest that IL6, VEGFA, and RELA could be the potential drug targets by inhibiting the NF-κB signaling pathway. Our in silico studies shed new insights into P. vulgaris and its ingredients, e.g., quercetin, as potential botanical drugs against COVID-19 AKI, and warrant further studies on efficacy and mechanisms.